Psychosocial distress among unpaid community health workers in rural Ethiopia: Comparing leaders in Ethiopia's Women's Development Army to their peers. (June 2019) - Maes, Kenneth; Closser, Svea; Tesfaye, Yihenew; Abesha, Roza
Abstract: There is a growing critical social science literature on volunteering in health programs in non-western, low-income countries, yet few have mixed quantitative and qualitative methods to examine the psychological and social wellbeing of unpaid community health workers in such contexts. We address this issue with data from unpaid community health workers (CHWs) and other women who comprise Ethiopia's state-organized Women's Development Army. We draw on qualitative and cross-sectional survey data collected between 2013 and 2016 to test links between various aspects of psychosocial and economic wellbeing and volunteer status in a rural context. We surveyed 422 adult women in Amhara state, 73 of whom were unpaid CHWs in the "Army". We also conducted interviews and focus group discussions with health officials, salaried Health Extension Workers, volunteer CHWs, and other adult women. Analyses of our qualitative and quantitative datasets show that volunteer CHWs are actually worse off than their peers in various psychosocial and economic respects, and that CHW recruitment processes are the most likely explanation for this difference. Additionally, the unpaid CHW position adds work to already burdened shoulders, and makes women—especially unmarried women—vulnerable to negative gossip and high levels of psychological distress. To a limited extent, the volunteer CHW position also bolsters married women's subjective socioeconomic status and confidence in achieving future gains in status. By showing that unpaid CHWs do not necessarily enjoy psychosocial benefits, and may experience harm as a result of their work, these findings reinforce the recommendation that CHWs in contexts of poverty be paid and better supported. Highlights: Many global health initiatives rely on unpaid, impoverished community health workers (CHWs). Unpaid CHWs in Ethiopia's Women's Development Army are worse off than their peers. The unpaid CHW position puts more work on already burdened shoulders. Unmarried, unpaid CHWs experience negative gossip and high levels of psychological distress. These findings underline the need for payment and other support for these workers.